Using ratings of perceived difficulty for balance exercise prescription and intensity progression - Alsubaie, Saud F.; Marchetti, Gregory F.; Sienko, Kathleen H.; Whitney, Susan L.; Furman, Joseph M.; Sparto, Patrick J. (Frontiers in Rehabilitation Sciences, 2026)
BackgroundBalance is a fundamental component of daily activities and plays a critical role in preventing falls. Balance can be influenced by a variety of factors, including age-related physiological changes, making it important to consider age when assessing balance performance. However, an empirical basis for estimating the difficulty of balance exercises has yet to be developed. The primary aim of this study was to determine the effect of age and different balance exercise conditions on difficulty of exercises as determined by self-reported perceived difficulty, and to show that Rating of Perceived Difficulty (RPD) can serve as a practical measure of difficulty for guiding balance exercise prescription and progression.MethodsSixty-two healthy adults between the ages of 20 and 85 years with a mean age of 55 ± 20 years (50% female) participated in this cross-sectional study. Subjects performed four 30 s trials of 24 static standing balance exercises, and the average of these four trials was used for analysis. For each exercise, subjects’ ratings of perceived difficulty (RPD) were recorded using a 0–10 scale.ResultsA significant increase in RPD across all balance exercises occurred as age increased (p < 0.02). From the youngest age group to the oldest, RPD increased by more than 100%. Ratings of perceived difficulty increased on a foam surface (110%), eyes closed (43%), semi-tandem stance (150%), and head movement (50%) compared with a firm surface, eyes open, feet apart, and head held still, respectively (p < 0.01).ConclusionRPD measurements across a range of standing balance exercises can be used as a measure of difficulty and a practical tool for prescribing and progressing balance exercises in rehabilitation programs.